Concepts of philosophy in Asia and the Islamic world - Steineck, Raji C. (Studien zur interkulturellen Philosophie / Studies in Intercultural Philosophy / Études de philosophie interculturelle, 2018)
The contributions to Concepts of Philosophy in Asia and the Islamic World reflect upon the problems implied in the received notions of philosophy in the respective scholarly literatures. They ask whether, and for what reasons, a text should be categorized as a philosophical text (or excluded from the canon of philosophy), and what this means for the concept of philosophy. The focus on texts and textual corpora is central because it makes authors expose their claims and arguments in direct relation to specific sources, and discourages generalized reflections on the characteristics of, for example, Japanese culture or the Indian mind. The volume demonstrates that close and historically informed readings are the sine qua non in discussing what philosophy is in Asia and the Islamic world, just as much as with regard to Western literature Contributors are Yoko Arisaka, Wolfgang Behr, Thomas Fröhlich, Lisa Indraccolo, Paulus Kaufmann, Iso Kern, Ralf Müller, Gregor Paul, Lisa Raphals, Fabian Schäfer, Ori Sela, Rafael Suter, Christian Uhl, Viatcheslav Vetrov, Yvonne Schulz Zinda, and Nicholas Zufferey.